Diagnostic accuracy and safety of Dermatophagoides pteronyssinus extracts used for skin prick test. Issue 21 (5th November 2022) - Tang, Rui; Lyu, Xiaohong; Liu, Yuxi; Wang, Ruiqi; Wang, Lianglu; Li, Hong; Sun, Jinlyu; Zhi, Yuxiang; Gu, Jianqing; Guan, Kai; Wen, Liping; Wang, Zixi; et al.
Abstract: Background: Dermatophagoides pteronyssinus is a common allergen causing allergic diseases in China. The aim of this study was to evaluate the efficacy and safety of D. pteronyssinus extracts produced by Peking Union Medical College Hospital (PUMCH) for the skin prick test (SPT) in the diagnosis of D. pteronyssinus allergy. Methods: A total of 910 subjects with allergic diseases were prescribed D. pteronyssinus SPT and specific sIgE (sIgE) test among the Outpatients of Department of Allergy, PUMCH from August 10, 2015 to August 30, 2017. Receiver operating characteristic curve (ROC) analysis was performed according to the results of D. pteronyssinus -sIgE detection. The accuracy of D. pteronyssinus extracts used for SPT in the diagnosis of D. pteronyssinus allergy was evaluated under different cutoff values. Adverse events after SPT were recorded to evaluate safety. Results: There were 796 and 618 subjects in the full analysis set (FAS) and the per protocol set (PPS), respectively. The areas under the curve of FAS and PPS were 0.871 and 0.873, respectively. According to the ROC of PPS, the optimal and 95% specificity diagnostic cutoff values of D. pteronyssinus SPT mean wheal diameter were 3.25 and 3.75 mm, respectively. No adverse events occurred. Conclusion: The extracts of D. pteronyssinus for SPT were simple, highly accurate, and safe and should be considered for recommendation in the clinical diagnosis of D. pteronyssinus allergy.